The Importance of ESP for Front office Staff - KERROUM, YASSINE (My University, 2020)
There is no doubt that skills in the language of another country are invaluable in communicating with people from that country. With English having become an international language, it makes sense that it is vital in the hospitality industry. When a person works in by a hotel, one can expect to have a good level of English…. ??. This research examines the importance of ESP training for hospitality industry personnel and the use of English by front office employees with politeness strategies. To conduct this research study, two data collection instruments were used in the four to five star "Jumeirah Beach Hotel" hotels in Dubai and in the "Al Mansour Palace" hotel in Mostaganem. An interview with the FO manager and the former FO manager for hotels and observations. The results revealed that ESP training at the Dubai hotel allows front desk staff to interact effectively and easily overcome communication challenges. However, the lack of this training in Algerian hotels leads to communication difficulties which reflect a bad reputation of local hotels.
Case study: AL Mansour Palace Hotel, Jumeirah Beach Hotel
Keywords: English for Specific Purposes (ESP); Hotel staff; Language skills